2021
DOI: 10.1177/0092055x211060344
|View full text |Cite
|
Sign up to set email alerts
|

Learning from 2020: How the Challenges of Remote Teaching Reinforce the Need for Care-Informed Pedagogy

Abstract: How did instructors design their sociology courses for remote teaching during the 2020–2021 academic year, and what challenges did they face in teaching those courses? To answer these questions, we surveyed lead instructors and graduate teaching assistants (n = 77) in the Sociology Department at the University of Michigan, supplemented by interviews with students and our experiences as remote course consultants. Through this case study, we found that instructors cited increased workload and lack of connection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…For example, research demonstrates that students in an online instruction environment reported that they felt cared for through instructor strategies such as establishing an active presence in the course by way of regular communication and feedback (Robinson et al, 2020). Instructors in one sociology department also identified instructional practices that aligned with a care-informed pedagogy (Hess et al, 2022). These included building community, increasing flexibility, and using formative assessments, which are practices that should continue to inform course design beyond the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research demonstrates that students in an online instruction environment reported that they felt cared for through instructor strategies such as establishing an active presence in the course by way of regular communication and feedback (Robinson et al, 2020). Instructors in one sociology department also identified instructional practices that aligned with a care-informed pedagogy (Hess et al, 2022). These included building community, increasing flexibility, and using formative assessments, which are practices that should continue to inform course design beyond the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges are compounded by the growing need to develop course strategies that support first-generation college students, who face unique challenges in sociology classrooms. Alongside these calls, scholars have urged for a reexamination of how strategies implemented during the challenging remote instruction year can enhance traditional in-person classes (Hess et al 2022). In response to these calls, this study assessed the effectiveness of three distinct types of PLP activities on students' confidence and ability to understand and apply foundational concepts from PLP activities prior to lecture instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Не дивно, що соціально-економічні розриви та прогалини для категорії особливо вразливих учнів значно зросли. Медична професія та інші професії, які навчають шляхом поступового стажування, також серйозно постраждали та змушені були внести кардинальні зміни (Hess, 2022). Студенти, які вступали на свої клінічні ротації, зазнали найрізкіших змін у своєму досвіді.…”
Section: вступ та сучасний стан досліджуваної проблемиunclassified